Darwin's Voyage Through the Province of Jurisprudence: A Beguiling Hypothesis - Petersson, Sandra (Victoria University of Wellington Law Review, 2001)
If we share a common ancestor, is it not reasonable to suppose the existence of common ancestral laws — at least at some point in our distant past? This paper proposes an (irreverent) evolutionist revision of John Austin's classification of law. In short, what if, instead of living next door to Jeremy Bentham, Austin had lived next door to Charles Darwin? How would that environment have changed Austin's analysis in The Province of Jurisprudence?